Enhanced Removal of Malachite Green Dye from Textile Wastewater using TiO₂ Modified Palm Kernel Shell Activated Carbon: Optimization and Mechanistic Assessment - Olowonyo Idayat. A; Sole-Adeoye Opeoluwa. D; Salam Kazeem. K; Aremu Mujidat. O; Oreofe Toyin. A; Akinwumi Odunayo. D; Owolabi Stephen. O (Candela Edutech Indonesia, 2025)
Malachite Green Dye (MGD), a toxic dye commonly discharged by textile industries, poses environmental and health risks. Simultaneously, the disposal of palm kernel shells (PKS), a byproduct of palm oil production, remains an underexploited resource. This study explores the use of activated carbon derived from PKS, modified with titanium dioxide nanoparticles (TiO2-NP), for the adsorption of malachite green dye from aqueous solution. The adsorbent was characterized for its structural and surface chemistry. Batch adsorption experiments were carried out to evaluate the effects of dosage (0.5-2.5 g), contact time (30-150 min), agitation (100-300 rpm), and temperature (30-60 °C). Process optimization was carried out using the Box-Behnken design under the Response Surface Methodology (RSM) framework. Additionally, kinetic and thermodynamic analyses were performed to gain insights into the adsorption mechanism. Numerical optimization revealed a maximum dye removal of 92.6%. Kinetic analysis supported pseudo-second-order behavior, indicating chemisorption, while thermodynamic data confirmed a spontaneous and endothermic process. The adsorbent showed effective regeneration over five cycles, maintaining high efficiency. The prepared adsorbent exhibited a fixed carbon content of 69.50%, while the presence of functional groups involved in dye binding was confirmed through FTIR analysis. These results underscore the potential of PKSAC-TiO₂ as a cost-effective and sustainable adsorbent for dye-laden wastewater treatment.